Cognitive processing speed in pediatric-onset multiple sclerosis: Baseline characteristics of impairment and prediction of decline. (December 2020) - Wallach, Asya I; Waltz, Michael; Casper, T Charles; Aaen, Gregory; Belman, Anita; Benson, Leslie; Chitnis, Tanuja; Gorman, Mark; Graves, Jennifer; Harris, Yolanda; Lotze, Timothy E; Mar, Soe; et al.
Background: Cognitive impairment occurs in approximately one-third of pediatric-onset multiple sclerosis (POMS) patients. The Symbol Digit Modalities Test (SDMT), a widely used cognitive screen in adults, has yet to be incorporated early into the standard care of POMS. Objective: To screen for cognitive impairment early in the course of POMS and analyze predictive factors. Methods: Of the 955 POMS or clinically isolated syndrome (CIS) patients prospectively assessed from March 2014 to July 2018, 500 POMS and 116 CIS patients met inclusion criteria (disease onset before the age of 18, one or more SDMTs, and 8 years or older at the time of testing). Those with relapse were analyzed separately from those who were relapse-free. Results: At initial assessment, the mean (interquartile range (IQR)) age at symptom onset was 13.5 years (12.0, 15.9) and the mean (±SD) disease duration was 3.0 ± 2.9 years. Impaired processing speed occurred in 23.4% of POMS and in 16.4% of CIS. On serial testing ( n  = 383, mean follow-up: 1.8 years), 14.1% had clinically meaningful decline predicted by older age of multiple sclerosis (MS) onset and male gender. Disease relapse or steroid use led to transient worsening on the SDMT. Conclusion: Early in the disease, some POMS and CIS patients are at risk for cognitive impairment and subsequent decline.